Application of Pt/CdS for the Photocatalytic Flue Gas Desulfurization - Xiulan Song; Weifeng Yao; Bo Zhang; Yiping Wu (International Journal of Photoenergy)
A photocatalytic flue gas desulfurization technology was designed to control emissions of SO2 from the combustion of fossil fuels. With the photocatalytic technology, we cannot only achieve the purpose of solving the problem of SO2 emissions but also realize the desire of hydrogen production from water. CdS loaded with Pt were selected as the model photocatalyst for the photocatalytic flue gas desulfurization. The factors influencing the rate of hydrogen production and ammonia sulfite solution oxidation were detected.